PENGGUNAAN EDMODO SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA - Vera Dewi Kartini Ompusunggu; Nilam Sari (JURNAL CURERE, 2019)
Along with the rapid development of the times, all aspects of life also changed. This is a challenge for educators to be able to use technology optimally and can facilitate interaction with students in the learning process, one of which is Edmodo. Edmodo is a social learning platform for teachers / lecturers and students / students that provides several features to support e-learning such as assignments, quizzes, assessments, etc. Through edmodo teachers and students can share notes and documents and can share discussions online. This study aims to describe the use of edmodo in analytic geometry learning in 5th semester students of the Mathematics Education study program at Quality University, Medan. This research is a qualitative research. Qualitative research is said because it is descriptive and tends to use analysis of research subjects that are highlighted. Analysis techniques used are reduction, presentation, and verification and conclusion. Validation using triangulation (combined). Reduction namely that has been obtained is reduced so that it gives a clearer picture and makes it easier for researchers to collect. Presentation is done in the form of brief description. Verification and drawing conclusions are new findings that have never before existed.